Knowledge Management in a Major Construction Firm in Taiwan: A Case Study- Examining the Impacts of KM Initiatives Within the Firm - Kuo, Chin Chin; Wu, Jeremy (International journal of knowledge, culture and change management, 2007)
This paper addresses knowledge management (KM) in a project management organisation through a case study. The case study organisation is a small-medium sized Taiwanese-owned construction company (staff size of approximately 50) with an annual turnover of approximately TWD50 (AUD$1.85) billion. Approximately one half of the company comprised project-related staff (e.g. construction project management, project documentation, estimation, procurement, and design), while the other comprised administrative and business-related staff (e.g. office administration and management, business development, and finance and accounting). The researcher undertook a series of surveys and one-on-one interviews whilst ‘embedded’ for several months with the organisation. As part of a larger research project, this case study was one of four case studies conducted in major construction organisations in Singapore, Taiwan, and Australia. The study revealed the recognition, importance and commitment of organisational culture to KM, and the effects the knowledge management initiatives have on the organisation’s ability to manage knowledge across its projects and deliver the projects at various ‘levels’ of the organisation (individual, project, departmental, and corporate). It concludes that a technologically and functionally sound KM infrastructure does not necessarily assure an organisation with a capability to manage knowledge. Organisations need to ensure that the KM repository is made up of quality and relevant contents (not just quantity), and that corporate culture (especially the willingness of individuals to share what they know) is a critical determining factor to the organisation’s ability to share, apply and create knowledge (i.e. low sharing capability leads to low application and creation capabilities).